MicroRNA-148a-3p is a candidate mediator of increased bone marrow adiposity and bone loss following spinal cord injury - Lincoln, Samantha; Morse, Leslie R.; Troy, Karen; Mattson, Nicole; Nguyen, Nguyen; Battaglino, Ricardo A. (Frontiers in Endocrinology, 2022)
Spinal cord injury (SCI) is often followed by the severe, rapid onset of bone loss resulting in osteoporosis, but the mechanisms mediating this process are not fully understood. The objective of this study was to investigate microRNA (miRNA) mediated mechanisms that contribute to the development of this condition. For this, we studied participants with acute SCI (n=12), chronic SCI (n=18), and controls without SCI (n=23). Plasma samples were obtained from all subjects and subjected to transcriptomic analysis to detect differentially expressed miRNAs. MiR-148a-3p was selected for further study due to its known involvement in pathways regulating bone and fat metabolism. CT scans of the knee were performed on all subjects with SCI and analyzed to determine bone marrow adipose tissue (MAT) volume. In subjects with acute SCI, plasma miR-148-3p was increased 1.36-fold compared to controls without SCI (p=0.02) and 1.41-fold compared to subjects with chronic SCI (p=.014). Femur diaphysis marrow adiposity was increased 2.26-fold in subjects with chronic SCI compared to subjects with acute SCI (p=0.02). A multivariate model showed that BMI and mir-148a-3p predicted femur diaphysis marrow adiposity. This model explained 24% of the variation in diaphysis marrow adiposity (R2=0.24, p=0.02). This study showed a significant increase in miR-148a-3p during the acute phase of SCI. We propose that this contributes to subsequent bone loss in individuals with SCI by promoting osteoclast differentiation and increasing bone resorption, as well as promoting adipogenesis and inhibiting osteogenesis in mesenchymal stem cells, leading to increased bone marrow adiposity and lower bone mineral density.